Characteristics of people with epilepsy in three Eastern African countries - a pooled analysis - Stelzle, Dominik; Kaducu, Joyce; Schmidt, Veronika; Welte, Tamara; Ngowi, Bernard J.; Matuja, William; Escheu, Gabrielle; Hauke, Peter; Richter, Vivien; Ovuga, Emilio; Pfausler, Bettina; Schmutzhard, Erich; et al. (BMC Neurology, 2022)
Background Epilepsy is one of the most common neurological disorders worldwide. Yet, its treatment gap is large in some areas and especially in sub-Saharan Africa data on clinical, radiological and semiological characteristics, as well as on treatment of persons with epilepsy (PWE) are still scarce. Methods We pooled data from four cross-sectional studies on epilepsy in eastern Africa. Two studies from Malawi and Uganda were community-based; two studies in Tanzania (urban Dar es Salaam and rural Haydom) were hospital-based. Clinical characteristics of PWE were assessed by the same questionnaire. Additionally, data on treatment were collected and computed tomography (CT) scans were performed. Results Overall, 1179 PWE were included in our analysis (581 (49.3%) female, median age 22 years (IQR 15-32 years)). Up to 25% of the patients had focal onset seizures. Those showed a higher rate of remarkable CT scan findings, with especially post-ischaemic and neurocysticercosis-associated lesions, compared to PWE with generalized onset seizures (35.1% vs. 20%). The majority of the patients experienced tonic-clonic seizures (70-85%). Only 67-78% of PWE received anti-seizure medication (ASM) treatment in the community-based studies, mostly monotherapy with phenobarbital, phenytoin or carbamazepine. Yet, underdosage was frequent and a large proportion of PWE received alternative non-ASM treatment consisting of herbal treatment (up to 83%) and/or scarification (up to 20%). Conclusions Epilepsy is common in sub-Saharan Africa, often caused by neurocysticercosis or ischaemic strokes. PWE suffer from high seizure rates and subsequent injuries, as well as from socio-economic consequences due to insufficient ASM treatment. This pooled analysis illustrates the need for structural programmes for adequate identification, education, assessment and treatment of PWE in sub-Saharan Africa.
CRIS-Team WoS Importer:2022-09-09